Designing an optimum shipping tax regime by applying an updated multi-analytical framework - Hitchens, Barry Grant (Department of Finance and Tax, 2023)
The thesis observes that taxes may be utilised for purposes other than revenue generation. The thesis submits that sea power should constitute a critical objective for designing an optimal shipping tax regime. This submission is partly based on considering the historical development of the American and British registered merchant fleets. The thesis observes that States compete under certain conditions despite globalisation. Therefore, sea power remains a valid underlying objective. The thesis submits that registered merchant vessels constitute a reasonable indicator for assessing a critical component of a State's sea power. The thesis advances the argument that shipping income should primarily be produced from the navigation of these vessels for carrying goods and passengers by sea. This feature of the maritime adventure supports the exceptional mobility of shipping income and is crucial for promoting a State's sea power. These activities are, therefore, primarily deserving of special tax treatment. The thesis constructs a Model Analytical Framework to support the design of an optimal shipping tax regime. The Smithian Framework is a key component. The latter is constructed to, broadly, accord with the tax design principles of the G20 States. The thesis utilises the 1998 OECD Framework assessing harmful tax practices and preferential regimes, as updated by BEPS 5, as the other key component. The significance of this other component is that its key factors should be satisfied for designing preferential regimes that have broader legitimacy internationally. The thesis ranks the benchmarked efficiency and simplicity criteria as dominant priorities to counter the high mobility of the particular tax base. The thesis applies super efficiency intensely to better level the playing fields between the local and foreign ship registers. The thesis observes that the substantial activity factor, as updated by BEPS 5, although having the potential to reduce the mobility of the tax base, is unlikely to do so without more. As a model for an optimal shipping tax regime that exhibits uniformity and simplicity extensively and can promote a State's sea power, the thesis recommends the basic Panamanian design incorporating broader features of the Greek regime.